Meningkatkan Aktifitas dan Keterampilan Interaksi Transaksional Lisan (Speaking) Melalui Penerapan Model Role Play pada Materi Nama Hari, Bulan, dan Waktu bagi Siswa Kelas VII - Suaidi, Suaidi (Educatoria : Jurnal Ilmiah Ilmu Pendidikan, 2023)
This research was conducted because the value of English was far from the specified Madrasah Maximum Completeness Criteria (KKM). Against the background of the low value of the English language, this research was conducted with the aim of increasing the activity of English speaking transactional interaction skills on the material names of days, months and times by using the role play model. This research was conducted from September to November 2017, taking place in class VII-8 MTs. Negeri 1 Mataram, Mataram City. This type of research is Classroom Action Research (CAR) with two cycles consisting of two meetings in one cycle, each cycle consisting of planning, implementing, observing and reflecting. Data collection techniques and tools in this study used descriptive analysis techniques for data in the form of student performance scores and observation sheets. The results showed that with the activity role play model and students' oral transactional interaction skills increased, that is, from the results of cycle I to Cycle II there was an increase where in cycle I the number of students who received a complete score was 23 students or 67.65%, the score was incomplete on cycle I was 11 students or 32.35%, while in cycle II there was an increase in the pass score, namely, to 23 students or 85.29% there was an increase of 17.64%. It was concluded that the role play model can improve English spoken transactional interaction skills.